Pengaruh Pembelajaran Akidah Akhlak Terhadap Tindak Perundungan Antar Siswa Kelas VIII SMP Islam Al-Fadhli - Syaiful Bahri, Amelia Ramdhani Syaiyuti; Maya Dita Anggraini; Dwi Sabrina Ummaya; Juliana; Pani Akhiruddin Siregar (Tarbawi, 2024)
Cases of bullying in the school environment are still a problem that continues to occur today. One of the causes of bullying in the school environment is the lack of student morale. The cultivation of character values is indispensable to overcome the moral crisis. The purpose of this study was to see how much influence Akidah Akhlak learning has on bullying between students. Using causal quantitative methods, samples were taken from the entire population, namely 36 junior high school students Islam Al-Fadhli. The analysis technique used in this study is simple linear regression through the formula: Y = a + bX, obtained by the equation Y = 6.582 - 0.612X. Because the value of the regression coefficient is positive (+) it can be concluded that Akidah Akhlak Learning affects bullying between grade VIII students of Al-Fadhli Islamic Junior High School Although through the results of this study, the influence of Akidah Akhlak learning on bullying in schools is still very small. However, this still has an impact in an effort to minimize bullying in schools..